Switching of the c-Myc protein degradation pathway depending on the PP2A-B55α complex levels - Sana Ando; Shunta Ikeda; Keiko Tanaka; Yuri Tomabechi; Atsushi Yamagata; Mikako Shirouzu; Ryouichi Tsunedomi; Hiroaki Nagano; Shunya Tsuji; Koichi Sato; Takashi Ohama (Proceedings of the National Academy of Sciences, 2026)
The transcription factor c-Myc is a master oncoprotein that regulates over 15% of all genes. Protein phosphatase 2A (PP2A), a crucial tumor suppressor, destabilizes c-Myc protein. Classically, PP2A-mediated dephosphorylation of Ser62 followed by Thr58 phosphorylation was thought to promote ubiquitination of c-Myc by the E3 ligase F-box and WD repeat domain containing 7 (FBXW7). However, recent evidence indicates that FBXW7 preferentially recognizes c-Myc when both Thr58 and Ser62 are phosphorylated, leaving the mechanism underlying PP2A-induced c-Myc degradation unsolved. Here, we demonstrate that the PP2A-B55α complex, which directly dephosphorylates c-Myc at Thr58, regulates two distinct degradation pathways in a biphasic manner: B55α suppression increases Thr58 phosphorylation and enhances FBXW7-dependent degradation, whereas B55α overexpression promotes Thr58-independent, ubiquitin-protein ligase E3 component N-recognin 5 (UBR5)-mediated degradation. We further show that the PP2A-B55α complex binds and dephosphorylates UBR5. In contrast, B55δ, which belongs to the same B55 family and shares a common core structure, exhibits weaker UBR5 binding affinity and fails to induce c-Myc degradation. Our findings identify PP2A-B55α as a context-dependent molecular switch for c-Myc degradation and provide a unified framework that resolves the paradox linking PP2A activation to c-Myc destabilization.